2014
DOI: 10.3109/10717544.2014.920430
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of nanoemulsion assisted oral delivery of docetaxel for improved chemotherapy of cancer

Abstract: Context: Nanoemulsions (NE) are one of the robust delivery tools for drugs due to their higher stability and efficacy. Objectives: The purpose of present investigation is to develop stable, effective and safe NE of docetaxel (DTX). Methods: Soybean oil, lecithin, Pluronic F68, PEG 4000 and ethanol were employed as excipients and NEs were prepared by hot homogenization followed by ultra-sonication. NEs were optimized and investigated for different in vitro and in vivo parameters viz. droplet size, poly dispersi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…The extent of NCs uptake in vitro was examined by flow cytometry (BD Biosciences, FACS Aria, Germany). The data are presented as the mean fluorescence obtained from a population of 10 000 cells 27,28 .…”
Section: Cellular Uptake Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The extent of NCs uptake in vitro was examined by flow cytometry (BD Biosciences, FACS Aria, Germany). The data are presented as the mean fluorescence obtained from a population of 10 000 cells 27,28 .…”
Section: Cellular Uptake Studiesmentioning
confidence: 99%
“…The limit of detection (LOD) and quantification (LOQ) were found to be 36 and 156 ng/ml, respectively. Following formula was used to calculate the entrapment efficiency 16,[25][26][27][28] .…”
Section: Entrapment Efficiency (%Ee)mentioning
confidence: 99%
“…In recent years, nanoemulsion systems have received increasing attention as an appropriate carrier system for insoluble active compounds to increase their bioavailability and modify drug release characteristics (Han et al, 2009;Kotta et al, 2013;Sharma et al, 2014;Verma et al, 2014). For instance, improved oral bioavailability of amlodipine (Chhabra et al, 2011) and felodipine (Veerareddy et al, 2012) nanoemulsions in comparison with the conventional preparations has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoemulsion systems have received increasing attention as appropriate carriers for insoluble active compounds to increase bioavailability and modify drug release characteristics. [13][14][15] Improvements in the solubility of drugs into nanoemulsion components such as the oil phase and surfactants represent an effective strategy for drugs for which low water solubility dissolution is the rate limiting step in absorption and bioavailability. However, non-ionic surfactants are inhibitors of intestinal P-gp.…”
mentioning
confidence: 99%